Co-pyrolysis of textile dyeing sludge and red wood waste in a continuously operated auger reactor under microwave irradiation. (1st March 2021) - Zhou, Chunbao; Zhang, Yingwen; Liu, Yang; Deng, Zeyu; Li, Xiangtong; Wang, Long; Dai, Jianjun; Song, Yongmeng; Jiang, Zhihui; Qu, Junshen; Siyal, Asif Ali
Abstract: The eco-friendly disposal of textile dyeing sludge (TDS) has become a worldwide environmental issue due to their complexity and toxicity. In this study, co-pyrolysis of TDS and red wood waste (RWW) in a continuously operated auger reactor under microwave irradiation was investigated, which was more environmentally friendly and created higher value added products. Effects of pyrolysis temperature and RWW ratio were studied to evaluate product distribution and properties. Increase of temperature and RWW ratio resulted in decrease in char yield and increase in gas yield. The contents of CO, CH4, and H2 increased significantly with RWW ratio increased at 650 °C. The content of pyridines, amines, and nitriles enhanced sharply with increasing temperature from 450 to 750 °C. Co-pyrolysis promoted the Maillard reaction and cracking of nitrogen-containing pigments, forming large quantities of N-heterocyclics in bio-oil. Sludge char obtained by pyrolysis of TDS at 650 °C had a greater sulfur retention ability than chars from co-pyrolysis. The highest methylene blue number (372.25 mg/g) and iodine adsorption value (332.42 mg/g) were achieved from TDS and biochar (750 °C, 30 wt% RWW ratio), respectively. Fe(III) in Fe2 O3 was reduced to Fe(II) in Fe3 O4 and further partially reduced to metallic Fe in biochar. Graphical abstract: Image 1 Highlights: CO2, H2, phenols increased with red wood waste (RWW) ratio during co-pyrolysis. The highest yields of H2 and pyridine were achieved at 650 °C with 45–60% RWW. The content of nitrogenated compounds reached 91.23% in oil (750 °C, RWW of 30%). Fe2 O3 was reduced to Fe3 O4 and Fe in char during co-pyrolysis. The highest MB (372 mg/g) and iodine number (332 mg/g) were reached for TDS and char.